2014
DOI: 10.1603/ec13468
|View full text |Cite
|
Sign up to set email alerts
|

Demographic Analysis of the Fitness of <I>Problepsis superans</I> (Lepidoptera: Geometridae) Feeding on Three Ligustrum (Lamiales: Oleaceae) Species

Abstract: Using the age-stage, two-sex life table, the effects of three ligustrum species, Ligustrum x vicaryi Hort., Ligustrum quihoui Carrière, and Ligustrum lucidum Aiton, on the fitness of Problepsis superans (Butler, 1885) (Lepidoptera: Geometridae) were assayed by considering life table parameters of P. superans at 27 +/- 1 degrees C, 70 +/- 5% relative humidity, and a photoperiod of 16:8 (L: D) h. The means and SEs of population parameters were calculated using the jackknife and bootstrap methods. The total devel… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

1
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 50 publications
1
2
0
Order By: Relevance
“…Furthermore, the survival rates of P. absoluta varied across different developmental stages after feeding on different host plants. The pattern observed was characterized by an initial increase followed by a subsequent decrease, which aligns with similar trends reported for other insect species such as Problepsis superans (Butler) (Lepidoptera: Geometridae) (Hu et al 2014) and P. opercula (Wang et al 2020) feeding on different hosts. In this study, no significant difference was found in survival rates of P. absoluta feeding on L. esculentum, S. tuberosum, and S. melongena, which is consistent with the finding reported by Li et al (2019).…”
Section: Discussionsupporting
confidence: 87%
“…Furthermore, the survival rates of P. absoluta varied across different developmental stages after feeding on different host plants. The pattern observed was characterized by an initial increase followed by a subsequent decrease, which aligns with similar trends reported for other insect species such as Problepsis superans (Butler) (Lepidoptera: Geometridae) (Hu et al 2014) and P. opercula (Wang et al 2020) feeding on different hosts. In this study, no significant difference was found in survival rates of P. absoluta feeding on L. esculentum, S. tuberosum, and S. melongena, which is consistent with the finding reported by Li et al (2019).…”
Section: Discussionsupporting
confidence: 87%
“…Life table parameters r, λ, and R 0 are used to estimate the growth and reproductive potential of insect populations [49]. Our analysis indicates that the experimental colony displayed either higher fecundity or a faster rate of development [50].…”
Section: Discussionmentioning
confidence: 96%
“…Usually, a higher fecundity or faster development rate (lower TPOP) will generate a higher intrinsic rate of increase (r) (Hu et al 2014), and vice versa. Our results showed a lower fecundity and longer development time of T. remus on S. litura eggs (186.90 eggs/female and 10.03 days, respectively) (Table 2) compared with those reared on S. frugiperda eggs (214.4 eggs/female and 9.0 days, respectively) (Bueno et al 2014) when the parental generation was reared on their respective primary hosts under the same temperature (28 ℃).…”
Section: Discussionmentioning
confidence: 99%